Decrease of postprandial endothelial dysfunction by spice mix added to high‐fat hamburger meat in men with Type 2 diabetes mellitus. Issue 5 (7th March 2013) - Li, Z.; Henning, S. M.; Zhang, Y.; Rahnama, N.; Zerlin, A.; Thames, G.; Tseng, C. H.; Heber, D.
Abstract Aims Consumption of a high‐fat diet has been demonstrated to promote endothelial dysfunction, possibly through an increase in lipid peroxidation and decrease in serum nitric oxide. The present study was designed to investigate whether consumption of a hamburger cooked with a polyphenol‐rich spice mixture will reduce postprandial lipid oxidation and endothelial dysfunction in men with Type 2 diabetes. Methods Twenty‐two subjects consumed burgers cooked with salt only (control burger) or with salt and spice mix (spice burger) in randomized order. The postprandial concentration of urinary malondialdehyde and nitrate/nitrite as well as the peripheral arterial tonometry score were determined. Results Eighteen subjects completed the study. Postprandial serum glucose, insulin and triglyceride concentrations were similar in all subjects after control burger or spice burger consumption. Urine malondialdehyde excretion in mmol/g creatinine was reduced by 31% (P < 0.001) after consuming the spice burger compared with the control burger. Two hours after consumption of the burgers, the peripheral arterial tonometry score was significantly different between control burger consumption (−9.7 ± 21.5%) and spice burger consumption (+18.0 ± 42.4%) (P = 0.025). Mean urinary nitrate/nitrite concentrations in urine collected during the 6 h after consumption of the control burger was 9.09 ± 5.7 mmol/g creatinine, but 12.37 ± 7.00 mmol/g creatinine after the spice burger (P = 0.053). Conclusion Adding a spice mix to hamburger meat prior to cooking resulted in a reduction in urinary malondialdehyde, an increase in urinary nitrate/nitrite and improvement of postprandial endothelial dysfunction in men with Type 2 diabetes. Therefore, cooking a hamburger with a polyphenol‐rich spice mixture may lead to potential cardiovascular benefits in patients with Type 2 diabetes mellitus.